The book of charlatans - Jawbarī, ʻAbd al-Raḥmān ibn ʻUmar, active 1216-1222 (Library of Arabic literature., 2021)
Uncovering the professional secrets of con artists and swindlers in the medieval Middle East The Book of Charlatans is a comprehensive guide to trickery and scams as practiced in the thirteenth century in the cities of the Middle East, especially in Syria and Egypt. Al-Jawbarī was well versed in the practices he describes and may have been a reformed charlatan himself. Divided into thirty chapters, the book reveals the secrets of everyone from "Those Who Claim to be Prophets" to "Those Who Claim to Have Leprosy" and "Those Who Dye Horses." The material is informed in part by the author's own experience with alchemy, astrology, and geomancy, and in part by his extensive research. The work is unique in its systematic, detailed, and inclusive approach to a subject that is by nature arcane and that has relevance not only for social history but also for the history of science. Covering everything from invisible writing to doctoring gemstones and quack medicine, The Book of Charlatans opens a fascinating window into a subculture of beggars' guilds and professional con artists in the medieval Arab world.